The prospects of business development in ornamental fish in Southeast Sulawesi, Indonesia - SUR MULYATI; TOMMY HERDIANTO; ACHMAD SUHERMANTO; ACHMAD SOFIAN (Society for Indonesian Biodiversity, 2022)
Abstract. Mulyati S, Herdianto T, Suhermanto A, Sofian A. 2022. The prospects of business development in ornamental fish in Southeast Sulawesi, Indonesia. Biodiversitas 23: 6413-6419. Ornamental fish is a potential commodity necessarily optimized to improve the welfare of society. One of the Indonesian provinces producing diverse species of ornamental fish to export is Southeast Sulawesi. This study aimed to evaluate the ornamental fish potentials and create an evaluation possibly implemented as a consideration to determine business development strategies. The method was a case study, collected data through observation, interviews, literature study, and internal and external conditions were analyzed using SWOT analysis. The study analyzed the potential, trade, and strategy for business development in ornamental fish in Southeast Sulawesi. The study discovers that 38 species are traded, and nine of them are dominantly traded. Moreover, there are six main species potentially cultivated due to the demand and stable production; they are Betok Kupang (Chrysietera cyanea), Capungan (Apogon sp.), Angel KKO (Cirrhilabrus sp.), Clown fish (Amphiprion ocellaris), Keling Rub (Cirrhilabrus sp.), and Letter six (Paracanthurus hepatus). The development of ornamental fish cultivation can be implemented with the S-O (strengths–opportunities) strategy that manages and protects the environment of ornamental fish, strengthens the capacity of fishers and stakeholders for environmentally friendly activities and export market orientation, and builds cooperation of fisherman, exporters, and stakeholders to develop business in ornamental fish by emphasizing local species with high economic values and market demands. These results can be a consideration in making decisions related to the development of ornamental fish.